Assessing Technical Competence in Surgical Trainees: A Systematic Review. Issue 6 (June 2015) - Szasz, Peter; Louridas, Marisa; Harris, Kenneth A.; Aggarwal, Rajesh; Grantcharov, Teodor P.
Abstract : Objective: To systematically examine the literature describing the methods by which technical competence is assessed in surgical trainees. Background: The last decade has witnessed an evolution away from time-based surgical education. In response, governing bodies worldwide have implemented competency-based education paradigms. The definition of competence, however, remains elusive, and the impact of these education initiatives in terms of assessment methods remains unclear. Methods: A systematic review examining the methods by which technical competence is assessed was conducted by searching MEDLINE, EMBASE, PsychINFO, and the Cochrane database of systematic reviews. Abstracts of retrieved studies were reviewed and those meeting inclusion criteria were selected for full review. Data were retrieved in a systematic manner, the validity and reliability of the assessment methods was evaluated, and quality was assessed using the Grading of Recommendations Assessment, Development and Evaluation classification. Results: Of the 6814 studies identified, 85 studies involving 2369 surgical residents were included in this review. The methods used to assess technical competence were categorized into 5 groups; Likert scales (37), benchmarks (31), binary outcomes (11), novel tools (4), and surrogate outcomes (2). Their validity and reliability were mostly previously established. The overall Grading of Recommendations Assessment, Development and Evaluation for randomized controlled trials was high and low for the observational studies. Conclusions: The definition of technical competence continues to be debated within the medical literature. The methods used to evaluate technical competence predominantly include instruments that were originally created to assess technical skill. Very few studies identify standard setting approaches that differentiate competent versus noncompetent performers; subsequently, this has been identified as an area with great research potential. Abstract : Supplemental Digital Content is Available in the Text.Despite the emergence and incorporation of competency-based education paradigms within surgical training programs, competency-based assessments have not evolved in parallel. Findings in this systematic review illustrate the current methods utilized to assess the technical competence of surgical trainees.